The Status of the Conceived Child and the Problem of Assisted Fertilisation - Morales Godo, Juan (2005)
Advances in science and technology are rapidly transforming many aspects of human life. In this context, the author argues that the law must act as a "bridge" between these advances and the values that society has privileged. Advances such as artificial insemination and extrauterine or in vitro fertilisation, which are emerging as alternatives for people who cannot conceive naturally, raise a number of ethical and legal challenges. This article analyses this issue from a legal perspective, without losing sight of the prevailing values of society. In this context, it examines the legal problems associated with artificial insemination, such as the legal presumption of paternity or post-mortem insemination, as well as surrogate motherhood, among others. On the other hand, the legal situation of in vitro fertilisation is also evaluated, discussing the extension of the criminal offence of abortion to these cases, as well as the implications of the improvement of the human species (eugenic selection) that may arise from this type of fertilisation.